The Imprisoned, Unspeakable Self: Silenced Sexuality in Henry James - Camarasana, Linda (Pivot: A Journal of Interdisciplinary Studies and Thought, 2014)
This essay analyzes Henry James’s The Bostonians (1886) as a novel, like several other works by James, that hints at but never fully articulates homosexual desire. The relationship between Boston feminist Olive Chancellor and her protégé, Verena Tarrant, is a study in self-silencing and repression. In particular, James subtly explores Olive Chancellor’s struggle with an internal prison, her suppressed homosexuality, which was likely James’s own sexual struggle as well. In addition, James’s literary style, his famously imposing and dense walls of verbiage attempt to articulate secrets without ever stating what’s hidden. Paradoxically, James’s voluminous wall of words calls the reader’s attention to what is silent in his characters and in James himself.